Pharmaceutical modulation of diffusion potentials at aqueous–aqueous boundaries under laminar flow conditions - Collins, C.; Strutwolf, J.; Arrigan, Damien (Wiley-VCH Verlag, 2011)
In this work, the modulation of the diffusion potential formed at the microfluidic aqueous–aqueous boundary by a pharmaceutical substance is presented. Co-flowing aqueous streams in a microchannel were used to form the stable boundary between the streams. Measurement of the open circuit potential between two silver/silver chloride electrodes enabled the diffusion potential at the boundary to be determined, which is concentration dependent. Experimental results for protonated propranolol as well as tetrapropylammonium are presented. This concept may be useful as a strategy for the detection of drug substances.